2015
DOI: 10.3171/2014.11.jns13295
|View full text |Cite
|
Sign up to set email alerts
|

Role of adjuvant or salvage radiosurgery in the management of unresected residual or progressive glioblastoma multiforme in the pre–bevacizumab era

Abstract: abbreviatioNs ARE = adverse radiation effect; GBM = glioblastoma multiforme; KPS = Karnofsky Performance Scale; MST = median survival time; OS = overall survival; PFS = progression-free survival; RPA = recursive partitioning analysis; RT = radiation therapy; RTOG = Radiation Therapy Oncology Group; SRS = stereotactic radiosurgery. obJect After initial standard of care management of glioblastoma multiforme (GBM), relatively few proven options remain for patients with unresected progressive tumor. Numerous repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 55 publications
1
25
1
2
Order By: Relevance
“…52,54 Younger patients may have improved procedural tolerance, but they also have better glioblastoma prognosis, making it challenging to assess true GK treatment impact. However, age independently predicted improved post-GK survival on multivariable modeling, which suggests younger patients may be better candidates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52,54 Younger patients may have improved procedural tolerance, but they also have better glioblastoma prognosis, making it challenging to assess true GK treatment impact. However, age independently predicted improved post-GK survival on multivariable modeling, which suggests younger patients may be better candidates.…”
Section: Discussionmentioning
confidence: 99%
“…We performed sensitivity testing with various size cutoffs but were unable to identify a threshold for significantly poorer outcomes. Numerous reports 5458 assert that SRS may be most suitable for small, focal, or nodular glioblastoma recurrences. Specifically, one large recent study found post-SRS OS to be significantly better for patients with <14 cm 3 of treatment volume.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the utilization of combination chemotherapy and radiosurgery, Niranjan et al [16] concluded that patients undergoing SRS had a mean 1- and 2-year OS of 37.9 and 16.7%, respectively. Currently, the treatment paradigm for primary high-grade malignant gliomas consists of maximal safe resection, followed by adjuvant chemoradiation with TMZ in able patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hudes et al [15] did not report grade 3 toxicity or need for reoperation in their phase I dose-escalation study regarding persistent or recurrent GBM. In a retrospective review, Niranjan et al [16] suggested that combination SRS and bevacizumab may limit the potential toxicity associated with radiotherapy while enhancing its benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation